Discovering the engagement levels at Company XYZ - Anderson, Jennifer L. (University of Wisconsin--Stout, 2018)
This study focuses on why employee engagement practices are extremely important in sustaining and growing an organization. In addition, this study focuses on what could happen if an organization does not measure and implement employee engagement practices. Measuring employee engagement utilizing a survey is one technique to help gather data and utilize for growth opportunities within an organization. It is imperative to establish what employee engagement means in order to properly address employee engagement practices. After conducting an assessment to measure employee engagement it is important to make sure results are determined and then implemented to ensure that employee engagement practices improve within any organization.
Keywords: Engagement (Philosophy); Employees; Organizational change